Fabrication and characterization of cinnamaldehyde-loaded mesoporous bioactive glass nanoparticles/phbv-based microspheres for preventing bacterial infection and promoting bone tissue regeneration - Chotchindakun, Kittipat; Pekkoh, Jeeraporn; Ruangsuriya, Jetsada; Zheng, Kai; Ünalan, Irem; Boccaccini, Aldo R. (Polymers, 2021)
Polyhydroxybutyrate-co-hydroxyvalerate (PHBV) is considered a suitable polymer for drug delivery systems and bone tissue engineering due to its biocompatibility and biodegradability. However, the lack of bioactivity and antibacterial activity hinders its biomedical applications. In this study, mesoporous bioactive glass nanoparticles (MBGN) were incorporated into PHBV to enhance its bioactivity, while cinnamaldehyde (CIN) was loaded in MBGN to introduce antimicro-bial activity. The blank (PHBV/MBGN) and the CIN-loaded microspheres (PHBV/MBGN/CIN5, PHBV/MBGN/CIN10, and PHBV/MBGN/CIN20) were fabricated by emulsion solvent extrac-tion/evaporation method. The average particle size and zeta potential of all samples were in-vestigated, as well as the morphology of all samples evaluated by scanning electron microscopy. PHBV/MBGN/CIN5, PHBV/MBGN/CIN10, and PHBV/MBGN/CIN20 significantly exhibited antibacterial activity against Staphylococcus aureus and Escherichia coli in the first 3 h, while CIN releasing behavior was observed up to 7 d. Human osteosarcoma cell (MG-63) proliferation and attachment were noticed after 24 h cell culture, demonstrating no adverse effects due to the presence of microspheres. Additionally, the rapid formation of hydroxyapatite on the composite microspheres after immersion in simulated body fluid (SBF) during 7 d revealed the bioactivity of the composite mi-crospheres. Our findings indicate that this system represents an alternative model for an antibacterial biomaterial for potential applications in bone tissue engineering.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Antibacterial activity; Bioactive glass nanoparticles; Bone tissue engineering; Cinnamon oil; Drug delivery systems; Emulsion solvent evaporation method; Polyhydroxyalkanoates